2021
DOI: 10.3389/fmars.2021.621151
|View full text |Cite
|
Sign up to set email alerts
|

Active Ecological Restoration of Cold-Water Corals: Techniques, Challenges, Costs and Future Directions

Abstract: Cold-water coral (CWC) habitats dwell on continental shelves, slopes, seamounts, and ridge systems around the world’s oceans from 50 to 4000 m depth, providing heterogeneous habitats which support a myriad of associated fauna. These highly diverse ecosystems are threatened by human stressors such as fishing activities, gas and oil exploitation, and climate change. Since their life-history traits such as long lifespan and slow growth rates make CWCs very vulnerable to potential threats, it is a foremost challen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 217 publications
0
15
0
Order By: Relevance
“…-The use of artificial structures (namely the cause of the disturbance, TAP pipeline), as in cold-water corals or deepsea restoration interventions due to operational issues (O'Connor et al, 2020;Montseny et al, 2021); -The relocation of the portions of the reefs that would have been lost during the laying of the TAP pipeline, following the transplanting fragmented dislodged colonies widespread in coral reef environments (Henry and Hart, 2005;Forrester et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…-The use of artificial structures (namely the cause of the disturbance, TAP pipeline), as in cold-water corals or deepsea restoration interventions due to operational issues (O'Connor et al, 2020;Montseny et al, 2021); -The relocation of the portions of the reefs that would have been lost during the laying of the TAP pipeline, following the transplanting fragmented dislodged colonies widespread in coral reef environments (Henry and Hart, 2005;Forrester et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The experience and methods developed in shallow coral active restoration represent a great opportunity to successfully address the challenges of restoring deeper similar ecosystems, such as cold-water coral habitats (Montseny et al, 2021). The advent of mitigation interventions on deeper ecosystems, broadly known as deep-sea restoration, poses new challenges related to habitat features, operational difficulties, and high costs (Van Dover et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…1 It, indeed, is a global project launched by the United Nations for the decade 2021-2030 (Decade on Ecosystem Restoration, 2021) 2 and is an integral part of the European Green Deal and the Mission Starfish 2030. 3 So far, some efforts have been made to restore degraded and threatened marine habitats (e.g., Boström-Einarsson et al, 2020;Cebrian et al, 2021;Montseny et al, 2021). In the Mediterranean Sea, several studies focused on the restoration of coralligenous formations (Fava et al, 2010;Forcioli et al, 2011;Montero-Serra et al, 2017;Topçu et al, 2018;Montseny et al, 2019;Pagès Escolà et al, 2020;Casoli et al, 2021), seagrass meadows (Pirrotta et al, 2015;Alagna et al, 2019;Da Ros et al, 2021;Mancini et al, 2021;Piazzi et al, 2021;Ventura et al, 2021), macroalgal forests (De La Fuente et al, 2019;Tamburello et al, 2019), and other vulnerable habitat-forming species (Baldacconi et al, 2010;Musco et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…CWCs are threatened by several anthropogenic activities (D'Onghia et al, 2016;Ragnarsson et al, 2016;Montseny et al, 2021). Among them, deep-sea fisheries directly affect CWC reefs (D'Onghia, 2019), up to an estimated 95-98% of the total coral cover (Gianni, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Considering that the research field on ecological restoration of deep-sea ecosystems is still in its infancy (Da Ros et al, 2019), only few studies focus on CWCs active restoration actions, as reported in the literature (Montseny et al, 2021). The transplantation of nubbins taken from healthy colonies or reared in aquaria into degraded coral grounds is the preferred restoration action (Da Ros et al, 2019 and references therein).…”
Section: Introductionmentioning
confidence: 99%